The Role of Work Motivation as Effect Intervening Variable of Intrinsic Reward, Supervision of Work and Satisfaction of Compensation on Employee Performance (A Sudy at Cooperatives in the City of Pekalongan) - Setiawan, Singgih; Sutarlan, Sulistiyani; Sumarno, Nurchayati (International Review of Management and Marketing, 2018)
This study aims to examine the effect of Intrinsic Reward, Supervision of Work & Satisfaction of Compensation on Employee Performance. In addition, this study also aims to examine the effect of Work Motivation as an intervening variable. To test the variable, the researcher chose Cooperatives in the city of Pekalongan as research object. The research was conducted by distributing questionnaires to 120 employees at fifteen cooperatives in the city of Pekalongan. Sampling research using probability sampling with simple random sampling technique. The result of this research shows that Intrinsic Reward, Supervision of Work & Satisfaction of Compensation have significantly positive effect on Employee Performance at Cooperatives in the city of Pekalongan. But Work Motivation as intervening variable weakens the effect of Reward Instrinsik, Supervision of Work & Satisfaction of Compensation on Employee Performance at Cooperatives in the city of Pekalongan. Keywords: Intrinsic Reward, Supervision of Work, Satisfaction of Compensation, Work Motivation, Employee Performance JEL Classifications: J3, M1